Capacity Building and Market Intervention for Refugees: A Study of Current and Future Direction towards Sustainable Refugee Management - Fauzan Fauzan; Helmi Helmi; Zulkifli Harza; Sri Oktavia (Andalas Journal of International Studies (AJIS), 2020)
The number of refugees has increased for a decade leading to seek an alternative approach to managing refugees globally. This research will explore the current management of refugees and future direction towards sustainably managing refugees. While the UNHCR has a role in particularly resettling refugees to developed countries, states also have the authority to integrate refugees with local people under the Refugee Convention in 1951. The methodology used is a quantitative study through a statistical descriptive analysis from secondary sources and literature reviews. The result shows that states are reluctant to have a new arrival of refugees into their territories, while the UNHCR currently faces difficulties in resettling refugees to third countries. As a result, refugees are waiting with uncertainty and without livelihood opportunities in transiting countries. In regards to this issue, it seems necessary to have a capacity building and market intervention for the future direction of sustainable refugee management through a partnership with private sectors under the SDGs and other global agenda. These will equip refugees with skill development to enhance self-reliance as well as labor opportunities entering the future market places.